Research Progress of Long Non-Coding RNA GAS5 in Malignant Tumors - Lin, Guohong; Wu, Tianzhun; Gao, Xing; He, Ziqin; Nong, Wenwei (Frontiers in Oncology, 2022)
With the completion of the whole genome sequencing project, awareness of lncRNA further deepened. The growth arrest-specific transcript 5 (GAS5) was initially identified in growth-inhibiting cells. GAS5 refers to a molecular of lncRNA that do not encode the mature protein but plays a crucial role in various human cancers as a bona fide tumor suppressor. In addition, GAS5 is also the host gene of several small nucleolar RNAs (snoRNA). GAS5 expression levels in tumor tissues are significantly reduced, leading to increased malignancy, poor prognosis, and drug resistance. Recent studies have demonstrated that GAS5 can interact with other nucleic acids by base-pairing to inhibit their translation, impacting signaling pathways, changing the level of intracellular autophagy, oxidative stress, and immune cell function in vivo. GAS5 participates in the regulation of proliferation, invasion, and apoptosis through the above molecular mechanisms. This article reviews the recent discoveries on GAS5, including its expression level in different tumors, its biological behavior, and its molecular regulation mechanism in human cancer. The value of GAS5 as a molecular marker in cancer prevention and treatment is also discussed.